PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Vani Amilia Dewi, 13.05.52.0133; Dwi Nugroho, Arief Himmawan (Students' Journal of Accounting and Banking, 2017)
The purpose of this research to clarify the effect of firm size and leverage to the completeness of the disclosure of financial statements with profitability as an intervening variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange period 2012 - 2015 totaling 150 companies. The samples using purposive sampling method. The analytical method used is path analysis. The results obtained in this study is firm size has a positive effect on profitability and leverage. Profitability does not affect the completeness of financial statements. Profitability can not intervene firm size variables and leverage to the completeness of financial statement disclosure. The conclusion of this study also explains the size of the company has a positive effect on the completeness of the financial statements. In this study also proved leverage does not affect the completeness of financial statement disclosure.Keywords: Firm Size, Leverage, Profitability and Completeness of Financial Statement Disclosure